2020
DOI: 10.14746/sr.2020.4.2.08
|View full text |Cite
|
Sign up to set email alerts
|

(Non-Human)animal Companionship: A Crucial Support for People During the Covid-19 Pandemic

Abstract: Background Human-animal interaction (HAI) offers benefits across physical, emotional, psychological, and social spheres of human functioning. The aim of this paper is to delineate how animal companionship, via provision of HAI benefits, offers vital support to people experiencing the COVID-19 pandemic and associated stressors. Method Each of the empirically supported types of HAI benefits – physical, emotional, psychological, and social – will be situated within a biopsychosocial framework of human functioning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 11 publications
0
43
0
8
Order By: Relevance
“…Criticisms of the biased media reporting of research pertaining to the impact of pet ownership on human health and well-being, particularly during the COVID-19 pandemic, point out the danger of setting pet owners up for failure and disappointment, ultimately increasing the risk of shelter relinquishment [ 3 ]. There are several reasons why pets may be beneficial and/or detrimental to owner health and well-being during the COVID-19 pandemic [ 4 ]. In some cases, the stress of the COVID-19 pandemic may compromise the human-animal relationship and could instigate or accelerate other issues.…”
Section: Introductionmentioning
confidence: 99%
“…Criticisms of the biased media reporting of research pertaining to the impact of pet ownership on human health and well-being, particularly during the COVID-19 pandemic, point out the danger of setting pet owners up for failure and disappointment, ultimately increasing the risk of shelter relinquishment [ 3 ]. There are several reasons why pets may be beneficial and/or detrimental to owner health and well-being during the COVID-19 pandemic [ 4 ]. In some cases, the stress of the COVID-19 pandemic may compromise the human-animal relationship and could instigate or accelerate other issues.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have explored the impact of quarantine and self-isolation due to disease outbreaks (including the COVID-19 pandemic) on humans for reviews see [ 4 , 5 , 6 ], but few studies have examined the impact on our companion animals (pets). Recent studies have reported that while pets provided their owners with a positive presence and support during the COVID-19 pandemic, some pets also showed stress-related behavioural changes due to the disruptions to their usual environment and routine [ 7 , 8 , 9 , 10 ]. Emerging pet behavioural issues along with other unique hardships pet owners face due to COVID-19 lockdowns (eg lack of access to animal supplies and services, exacerbated financial/economic issues) increases the risk of inadequate care and relinquishment or abandonment, resulting in negative impacts on the well-being of both the owner and pet [ 7 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study investigated the impact of the nationwide lockdown on pet wellbeing in New Zealand as perceived by pet owners and discusses strategies to mitigate issues experienced by pet owners and to reinforce positive human behavioural changes that strengthen the human-animal bond, thus improving both animal and human wellbeing. Given that there is evidence that positive relationships with companion animals can be beneficial to the health and wellbeing of their owner and mitigate some of the detrimental effects of the COVID-19 lockdowns [ 7 , 8 , 9 , 10 ], this One Welfare approach promotes healthy communities during a global pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Hoy-Gerlach et al pointed out our interactions with pets could also be valuable in enhancing opportunities for physical exercise and activity [ 10 ]. Research on dog walking has pointed out that it is a valuable motivator to support adherence to exercise and can foster good physical and mental health [ 11 ].…”
Section: The Roles Of Animals Acting As Social Supportmentioning
confidence: 99%
“…Numerous commentaries suggested several issues including the economic and care burdens experienced by families taking care of their pets, the identified changes in their daily routines (including pets) as a result of being sequestered, and the healthcare concerns of the pets [ 12 ]. Nevertheless, throughout the globe, agencies are establishing food banks for the growing number of people who cannot afford pet food and supplies as well as arranging for foster care in the event of illness or inability to take care of their animals [ 10 ].…”
Section: The Roles Of Animals Acting As Social Supportmentioning
confidence: 99%